Comparison of outcomes of dual-mobility cemented total hip arthroplasty versus bipolar cemented hemiarthroplasty in patients with femoral neck fractures - Elsadany, Shady G.; Salama, Khaled S.; Elgreatly, Mohamed E.; Abdelaziz, Mohamed (International Journal of Research in Orthopaedics, 2024)
Background: Elderly people with femoral neck fractures are more likely to experience complications after hip replacement. Compared with total tripolar hip arthroplasty (THA), bipolar hemiarthroplasty (HA), more effective alternative treatments that improve overall safety. We aimed to review the benefits of dual mobility tripolar arthroplasty and compare it to bipolar hemiarthroplasty in treatment of the femoral neck in the elderly. Methods: This study was conducted as a comparative randomized controlled prospective study. Patients were divided randomly to two equal groups 19 patients each one group underwent cemented bipolar hip hemi arthroplasty and the other group underwent cemented tripolar total hip arthroplasty, surgical approach for the two study groups was modified lateral Hardinge approach. The patients were followed up after one month, three months 6 months and one year. The follow up period was one year, and modified Harris hip score was reported, and radiograph scan of fracture site was done before and after surgery. Complications were reported whether intraoperative or in the follow up period. Results: The result of the study showed that the operative time was much longer in tripolar group as compared to bipolar group, there was more blood loss in tripolar group more than bipolar group. The functional outcome assessed using Harris hip score showed better outcome in tripolar group as compared to bipolar group. As regard complication, there was one case of periprosthetic fracture intraoperative in bipolar group and one case of cement extrusion in tripolar group. There was no dislocation in both groups. Conclusions: Tripolar total hip arthroplasty had better functional outcome than bipolar hip hemiarthroplasty and we recommend more studies for a longer period of follow up to assess rate of complications and functional outcome on the long run.